Moderasi Beragama di Sekolah Menengah: Studi Kasus Interaksi Siswa Muslim dan Non-Muslim di SMPN 2 Ampek Nagari - Syafrudin; Iswantir; Julian Marfal (Jurnal Pustaka Cendekia Pendidikan, 2025)
This research discusses the practice of religious moderation at SMPN 2 Ampek Nagari, a secondary school with Muslim students as the majority and non-Muslim students as the minority. The aim of the research is to describe social interactions between Muslim and non-Muslim students, analyze the role of teachers in instilling the value of religious moderation, and identify challenges that arise in the process. This research uses descriptive qualitative methods with data collection techniques in the form of observation, in-depth interviews and documentation. The research results show that social interactions between Muslim and non-Muslim students are harmonious, characterized by cooperation in academic and non-academic activities without discrimination. Teachers play an important role as facilitators, role models and mediators in instilling tolerant attitudes through religious learning, citizenship education and other school activities. However, challenges were also found in the form of negative stereotypes brought from the family environment, as well as feelings of awkwardness in dealing with differences in religious practices. These findings confirm that schools function as laboratories for religious moderation, but their success requires support from parents and the community. Thus, the experience of SMPN 2 Ampek Nagari can become a model for implementing inclusive religious moderation for other secondary schools in Indonesia.